Designing kinestics for architectural facades: state change - Moloney, Jules
Architectural facades now have the potential to be literally kinetic, through automated sunscreens and a range of animated surfaces. This book explores the aesthetic potential of these new types of moving facades. Critique of theory and practice in architecture is combined here with ideas from kinetic art of the 1960?s. From this background the basic principles of kinetics are defined and are used to generate experimental computer animations. By classifying the animations, a theory of kinetic form called ?state change? is developed. This design research provides a unique and timely resource for those interested in the capacity of kinetics to enliven the public face of architecture.